Shopping Lifestyle Generasi Millenial dalam Trend Preloved Fashion - Meliana Rizkila; Adila Sosianika; Arie Indra Gunawan (Prosiding Industrial Research Workshop and National Seminar, 2021)
Shopping Lifestyle Generasi Millenial dalam Trend Preloved Fashion